Identification of Barriers and Lack of Facilitators of Nursing Process in Tertiary Care Hospitals of Lahore - Kaleem, Sadia; Hussain, Noreen Dilber; Ashraf, Zunaira (Biological and Clinical Sciences Research Journal, 2025)
The nursing process is a core framework of professional nursing practice that enhances the quality, safety, and consistency of patient care. Despite its inclusion in nursing curricula and global recognition, its implementation in clinical settings in Pakistan remains inconsistent. Objective: To identify the barriers and lack of facilitators affecting the implementation of the nursing process among nurses working in tertiary care hospitals in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted over four months (Dec 2024–Mar 2025) across three tertiary hospitals: Shaikh Zayed Hospital, Sir Ganga Ram Hospital, and Punjab Institute of Cardiology. A total of 133 registered nurses were selected through convenience sampling. Data were collected using a structured, self-administered questionnaire containing validated barrier and facilitator scales based on a 5-point Likert scale. Data analysis was performed using SPSS version 25. Results: All participants (100%) reported excessive barriers to implementing the nursing process, while 89.5% reported excessive facilitators. Major barriers included inadequate nurse-to-patient ratios (91%), purposelessness of care plans (84.2%), and heavy documentation. Facilitators such as educational preparation were acknowledged, yet essential supports like adequate time (only 3% neutral or positive) and access to resources were largely missing. Conclusion: Despite some level of training and awareness, systemic constraints hinder the effective implementation of the nursing process in Pakistani tertiary care settings. Addressing staffing shortages, improving administrative support, and enhancing access to clinical resources are critical to promoting structured, process-based nursing care.